(Re)imaginando passados emancipados: contranarrativas de liberdade em "Um defeito de cor" e "Beloved" - Cátia Cristina Bocaiuva Maringolo (2020)
The aim of this thesis is to (re)think the novels Um defeito de cor (2014), by Ana Maria Gonçalves and Beloved (1987, 2004), by Toni Morrison from a Black Feminist Literary Criticism approach, with an emphasis on the issues of memory, history and the concepts of archive, counterarchive, counter narrative and master narratives. We are interested in analyzing the representations of Black female characters in the novels and the status of their self-definition while rejecting and subverting negative, exclusionary and oppressive stereotypes, demonstrating the necessity of understanding, analyzing and interpreting literary works through different points of view, through the questioning of the notions of tradition, canon and universality/universal. In this sense, the analyzed novels are considered archival novels, resulting from a dialogue among memory, history, biography, fiction and Black Feminist Literary critique. We intend to confront and interpret the novels with the slave narratives of freed writers and the neo-slave narratives (contemporary narratives about enslavement and freedom) in order to establish convergent and divergent points regarding the construction of the characters from an intersectional perspective. We believe that the novels’ counter-narratives, in dialogue with the narratives of ex-enslaved and freed writers in the nineteenth century and Black Literature, create, tension and reimagine historiographies about slavery from a contemporary standpoint by establishing freedom counter-archives.